Vector Model for the Text Style Analysis - Darchuk, N.P.; Vasileva, I.V.; Vasilev, A.N. (Ukrainian Journal of Physics, 2021)
The application of physical approaches to the analysis of the authorial styles of Ukrainian writers has been considered. A model, where the literary styles are described in a multidimensional space with the help of unit vectors, is proposed. The numerical characteristic of the style is the scalar product of the corresponding vector and a vector that determines the general style for a group of authors. This parameter is shown to depend linearly on author’s rank. This behavior confi rms the hypothesis of joining the majority, according to which an author, when selecting his/her literary style, takes the style of his/her successful colleagues into account.